ANALISIS FAKTOR RISIKO KEJADIAN KETUBAN PECAH DINI PADA IBU BERSALIN: PENELITIAN CASE-CONTROL - Amrina Rohmah; Lusiana Ambarsari; Shinta Alifiana Rahmawati (Rena Cipta Mandiri, 2026)
Premature rupture of membranes (PROM) is one of the pregnancy complications that can increase maternal and neonatal morbidity and mortality. This study aimed to analyze the association between maternal age, education, occupation, parity, gestational age, anemia status, history of diabetes mellitus, and history of PROM with the incidence of PROM. A case-control design was employed using secondary data from 346 respondents, consisting of 173 cases and 173 controls. Data were analyzed using the Chi-square test with a 95% confidence level (α = 0.05). The results showed significant associations between maternal age (p = 0.025), education (p = 0.000), parity (p = 0.001), gestational age (p = 0.000), anemia status (p = 0.000), and history of PROM (p = 0.000) with the incidence of PROM. In contrast, occupation (p = 0.274) and history of diabetes mellitus (p = 0.200) were not significantly associated with PROM. It can be concluded that certain maternal and obstetric factors are associated with the incidence of PROM. Therefore, optimal antenatal monitoring is necessary to identify and manage these factors in order to reduce the risk of PROM.